Estimation of cotyledon isoflavone abundance by a grey luminance‐based model in variously hilum‐coloured soybean varieties. (3rd March 2016) - Barion, Giuseppe; Mosca, Giuliano; Vamerali, Teofilo
Abstract: BACKGROUND: The nutraceutical uses of soybean ( Glycine max L. Merr.) have received increasing attention in recent years, due to the therapeutic effects of high seed isoflavone concentrations against heart disease, cancer and menopausal symptoms. RESULTS: We found a close correlation between seed isoflavone abundance and hilum colour in a set of 17 contrasting soybean varieties. Image analysis of the hilum grey level pattern allowed us to identify a power model which approximates total cotyledon isoflavone concentrations (TCIC) at 65–71% by the normalised modal grey level. Higher TCIC levels were assigned to darker hilum varieties and vice versa within a variety‐dependent response. Optimisation of the algorithm required correction for a few specific varieties falling in the intermediate 1.1–1.5 mg g −1 TCIC range, which were over‐estimated by the model, perhaps due to variations in hilar optical properties related to the geometric features of both hilum and seed. CONCLUSION: In view of its easy, low‐cost detection, seed hilum colour is a useful phenotypic trait in soybean for rapid evaluation of isoflavone abundance in food uses and for improving specific nutraceutical breeding programmes. © 2016 Society of Chemical Industry